Imagining the Nation from the Outside : The Imagination of South Korea by Hallyu Content Consumers in Spain and Their Student Migration - Monllor, Maria (My University, 2024)
Among the many effects of the Hallyu phenomenon (the international popularity boom of South Korean popular culture, especially of K-pop and K-dramas) its positive effects on the improvement of South Korea’s national image abroad have been widely reported. Through in-depth interviews with seven Spanish Hallyu consumers pursuing migration in Seoul and Incheon, I explored their imagination of South Korea, its connection with Hallyu, and how it is impacted by the juxtaposition of imagination and personal experiences in South Korea during student mobility. Unexpectedly, participants showcased anxiety and fear towards their upcoming experiences as exchange studies in South Korea due to the presence of a negative imagination of the nation mediated mostly through social media influencers’ content circulating online. Furthermore, participants imagined South Korea pessimistically due to K-drama and K-pop consumption. This showcases the need to reevaluate the advantages and limitations of transnational popular consumption in its outcomes nation’s image formation.
Keywords: Hallyu, international student mobility, imagined nation, social media influencers, South Korea, Spain